Combining sclerostin neutralization with tissue engineering: An improved strategy for craniofacial bone repair. (1st March 2022) - Maillard, Sophie; Sicard, Ludovic; Andrique, Caroline; Torrens, Coralie; Lesieur, Julie; Baroukh, Brigitte; Coradin, Thibaud; Poliard, Anne; Slimani, Lotfi; Chaussain, Catherine
Abstract: Scaffolds associated with different types of mesenchymal stromal stem cells (MSC) are extensively studied for the development of novel therapies for large bone defects. Moreover, monoclonal antibodies have been recently introduced for the treatment of cancer-associated bone loss and other skeletal pathologies. In particular, antibodies against sclerostin, a key player in bone remodeling regulation, have demonstrated a real benefit for treating osteoporosis but their contribution to bone tissue-engineering remains uncharted. Here, we show that combining implantation of dense collagen hydrogels hosting wild-type (WT) murine dental pulp stem cells (mDPSC) with weekly systemic injections of a sclerostin antibody (Scl-Ab) leads to increased bone regeneration within critical size calvarial defects performed in WT mice. Furthermore, we show that bone formation is equivalent in calvarial defects in WT mice implanted with Sost knock-out (KO) mDPSC and in Sost KO mice, suggesting that the implantation of sclerostin-deficient MSC similarly promotes new bone formation than complete sclerostin deficiency. Altogether, our data demonstrate that an antibody-based therapy can potentialize tissue-engineering strategies for large craniofacial bone defects and urges the need to conduct research for antibody-enabled local inhibition of sclerostin. Statement of significance: The use of monoclonal antibodies is nowadays broadly spread for the treatment of several conditions including skeletal bone diseases. However, their use to potentialize tissue engineering constructs for bone repair remains unmet. Here, we demonstrate that the neutralization of sclerostin, through either a systemic inhibition by a monoclonal antibody or the implantation of sclerostin-deficient mesenchymal stromal stem cells (MSC) directly within the defect, improves the outcome of a tissue engineering approach, combining dense collagen hydrogels and MSC derived from the dental pulp, for the treatment of large craniofacial bone defects. Graphical abstract: Image, graphical abstract